Impacts of process and design conditions of dry stirred milling on the shape of product size distribution. (15th March 2021) - Altun, Okay; Prziwara, Paul; Breitung-Faes, Sandra; Kwade, Arno
Highlights: Variation in the shape of product size distribution was discussed for dry stirred media mill. Bead density, bead size, feed rate and tip speed parameters were adjusted in the milling. Different designs of dry stirred milling were compared. Stress energy of the mill and mean residence time of the particles were considered. Stirred mill is able to adjust the shape of the distribution. Abstract: A grinding technology should consider the physical properties of the material, i.e., size, shape, which have effects on the product specifications, i.e., quality, strength or overall process efficiency. In this respect, this study aimed at evaluating the variations in the shape of product size distribution of a stirred media mill as the attention on this technology has been growing in the recent years. Within the scope of the research, series of grinding tests were performed at different operating conditions, i.e. bead size, bead type, tip speed, feed rate and mill design, with a laboratory scale continuously operated horizontal stirred media mill. The investigations proved that the use of coarser and denser beads as well as adjusting higher tip speeds resulted in obtaining narrower product size distribution for the same mean size. For a better understanding of the process, the stress energy and mean residence time evaluations were also undertaken. It was found that the stress energy and its normalization with the mean residence time are directly proportional to the slope of the distributions. As a conclusion, the dry stirred media mill is able to adjust the shape of the distribution, which may be beneficial regarding to the mechanical properties of the end products (cement manufacturing) or efficiency of the mineral beneficiation processes.